2021
DOI: 10.1177/03080226211026554
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ experience of being involved with the transfer of the CO-OP approach: A qualitative study

Abstract: Introduction Since mothers are the best persons to facilitate transfer in their children, it is important to understand their experience with implementing the cognitive orientation to daily occupational performance approach at home. Therefore, this study aims to explore mothers’ experiences in facilitating transfer during implementing cognitive orientation to daily occupational performance approach at the home in children with specific learning disorder. Method A semi-structured interview was applied for mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The strengths‐based approach to intervention is consistent with our personal and professional views as paediatric physical therapists as well as recent evidence and commentaries in the field of CP, where focussing on and promoting strengths is recommended in contrast to interventions that simply target body structural impairments (Rosenbaum & Dan, 2020). The value of a strengths‐based focus has been reported in previous qualitative studies with mothers participating in an occupational therapy intervention (Gharebaghy et al, 2022) and health care providers of infants recently diagnosed with perinatal stroke (Khan et al, 2022). A systematic review of parent‐delivered therapy for children with CP found that seeing improvements in their child's function was a powerful external motivator to continue to pursue the intervention (Lord et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…The strengths‐based approach to intervention is consistent with our personal and professional views as paediatric physical therapists as well as recent evidence and commentaries in the field of CP, where focussing on and promoting strengths is recommended in contrast to interventions that simply target body structural impairments (Rosenbaum & Dan, 2020). The value of a strengths‐based focus has been reported in previous qualitative studies with mothers participating in an occupational therapy intervention (Gharebaghy et al, 2022) and health care providers of infants recently diagnosed with perinatal stroke (Khan et al, 2022). A systematic review of parent‐delivered therapy for children with CP found that seeing improvements in their child's function was a powerful external motivator to continue to pursue the intervention (Lord et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…Previous research on children with difficulties shows that the most effective services emphasize the role of the family in treatment [ 20 , 21 ]. On the other hand, recent qualitative studies on families of children with SLD have stated that improving mothers' learning needs facilitates the teaching of new skills and the solution of problems related to their child's occupational performance [ 22 , 23 ]. Therefore, empowering mothers of children with SLD, in addition to alleviating the burden and saving time and energy to manage their children compared to their siblings, improves the child's responsibility and participation in daily activities by teaching and learning necessary skills such as executive function skills.…”
Section: Introductionmentioning
confidence: 99%